Sintered metal filter medium, preparation method thereof, filter element and supercritical carbon dioxide filtering method
By introducing porous pinned nodes into the sintered metal filter medium, the problem of cracking in the sintered metal filter medium during post-processing is solved, resulting in a lower cracking rate and higher mechanical strength, making it suitable for high-pressure filtration conditions.
Patent Information
- Application Number
- CN202511492598.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2025-08-31
- Filing Date
- 2025-10-20
- Publication Date
- 2025-11-18
- Estimated Expiration
- 2045-10-20
AI Technical Summary
Existing sintered metal filter media are prone to cracking in post-processing steps, especially during cutting and welding, which affects the yield of filter elements.
By introducing pinned nodes from a porous structure into the sintered metal filter medium, controlling the particle size to be above 0.4μm, the average particle size to be 0.5-2.6μm, the surface distribution density to be 1-10 nodes per 10 square micrometers, and the area ratio not exceeding 85%, and combining with an appropriate degree of sintering, hard and soft areas are formed to improve mechanical strength and stress uniformity.
It significantly reduces the probability of cracking of sintered metal filter media in post-processing steps, ensuring the integrity of the filter element and its mechanical stability under high-pressure filtration conditions.
Smart Images

Figure CN120960875A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of filtration materials technology, and in particular to sintered metal filter media and their preparation methods, filter elements, and methods for filtering supercritical carbon dioxide. Background Technology
[0002] Sintered metal filter media are made from metal powder as raw material, formed through pressing / spraying / deposition filtration and further sintered at high temperature. They can be used to separate impurities in fluids and achieve precision filtration. For example, they can be used to filter high-purity fluids required by the semiconductor and microelectronics manufacturing industries, as well as high-purity fluids required for etching, cleaning and other surface manufacturing processes.
[0003] The fluid can be in the form of gas or liquid, or in the form of supercritical fluid, such as supercritical carbon dioxide. Filtering supercritical carbon dioxide requires relatively harsh supercritical conditions, such as temperatures above 30°C and pressures exceeding 25MPa, 30MPa, 35MPa, or even 40MPa. This places extremely high demands on the pressure resistance of the filter element. Sintered metal filter media, due to their high mechanical strength, are suitable for filtering such high-pressure fluids.
[0004] USRE36249E1 discloses a high-porosity metal membrane filtration device for gas purification in the semiconductor industry. The method for preparing the high-porosity metal membrane element includes: depositing a substantially uniform low-density sinterable dendritic material bed into a mold suitable for applying compressive force; compressing the low-density bed of sinterable dendritic material to form a green compact; and finally sintering the green compact at a temperature below the melting point of the metal material. The porous metal membrane element obtained by this method is sheet-like. When increasing production scale requires increasing the filtration area of the sheet-like porous metal membrane element, the overall volume of the filtration device becomes very large, making it unsuitable for the highly integrated installation and production line environment of semiconductor manufacturing processes.
[0005] To address the shortcomings of existing sheet-like porous metal filter media elements in terms of their inconvenience in expanding the filtration area, hollow tubular sintered metal filter media have been developed.
[0006] However, the production of filter cartridges from sintered metal filter media requires post-processing steps such as cutting and welding. For example, excess material at both ends of the sintered metal filter media is removed using a cutting tool to obtain the required dimensions. The sintered metal filter media of the determined dimensions is then welded together with plugs or housing components to obtain the final filter cartridge. During these post-processing steps, such as cutting, the sintered metal filter media often experiences unpredictable cracking, significantly limiting the yield of the filter cartridges.
[0007] Therefore, there is a need to provide a sintered metal filter medium that has a lower probability of cracking in post-processing steps. Summary of the Invention
[0008] To reduce the cracking rate of sintered metal filter media in post-processing steps, especially cutting steps, this application provides a sintered metal filter media and a method for preparing the same. It also provides a filter element including the sintered metal filter media and a method for filtering supercritical carbon dioxide.
[0009] A sintered metal filter medium includes at least a fine layer, the sintered metal filter medium having a hollow tubular structure; wherein, the fine layer has a porous structure, and the porous structure of the fine layer has pinned nodes, the particle size of the pinned nodes is not less than 0.4 μm, the average particle size of the pinned nodes is 0.5-2.6 μm, the surface distribution density of the pinned nodes is 1-10 per 10 square micrometers, and the area ratio of the pinned nodes does not exceed 85%; the initial bubble point (IPA) of the sintered metal filter medium is 50-500 kPa.
[0010] It is generally believed that cracking in sintered metal filter media is caused by poor mechanical strength or uneven stress. Therefore, the probability of cracking can be reduced by improving its mechanical strength and stress uniformity. The degree of sintering of the metal filter media can be controlled by regulating the sintering process. For example, increasing the degree of sintering, creating coarser sintering necks between metal particles, can improve its mechanical strength; while using raw materials with narrower and more uniform particle size distribution can improve the stress distribution uniformity of the metal filter media. Therefore, reducing the particle size distribution width of the metal particles and appropriately increasing the degree of sintering is generally considered to yield sintered metal filter media with a lower probability of cracking.
[0011] Accordingly, based on the above understanding, fine-layered metal particles with smaller particle size and narrower particle size distribution should be used, along with an appropriately increased degree of sintering, to improve the strength and stress uniformity of the fine layers of the sintered metal filter medium. The resulting sintered metal filter medium will naturally have higher strength and will not easily develop localized weak points due to stress concentration. It will also be less prone to cracking during subsequent processing, and even if localized microcracks do occur, they will not easily propagate further through certain stress concentration points, thus solving the problem of cracking of the sintered metal filter medium during the cutting process.
[0012] However, the inventors of this application discovered that the technical solutions intended to solve the cracking problem of metal filter media in post-processing steps did not actually solve the cracking problem; and due to the slightly higher degree of sintering and the smaller particle size of the fine-layered metal particles, the final metal filter media had a smaller pore size, resulting in good retention capacity but a significant decrease in flux. Conversely, the inventors unexpectedly discovered that when the final sintered metal filter media contained significantly larger pinned nodes with a particle size of not less than 0.4 μm and an average particle size of 0.5-2.6 μm in the porous structure of the fine layers, and the surface distribution density was 1-10 nodes per 10 square micrometers, with the area of the pinned nodes not exceeding 85%, the cracking phenomenon of the sintered metal filter media in post-processing steps was significantly reduced.
[0013] The unexpected aspect of this result is that larger pinned nodes, due to their smaller specific surface area and poorer diffusion rate, inevitably lead to an increase in the sintering driving force required for the surrounding fine-layer metal particles. This results in two main consequences: firstly, a decrease in the sintering uniformity across the fine layer, which often implies a further increase in stress non-uniformity; and secondly, a decrease in the degree of sintering around the pinned nodes, which inevitably leads to a decrease in the overall mechanical strength of the fine layer. Regardless of the increase in stress non-uniformity or the decrease in mechanical strength, the expected effect should be an increase in the cracking probability of the sintered metal filter media, rather than a result of achieving a lower cracking probability.
[0014] The reason why the special scheme in this application can significantly reduce the cracking rate may be due to: The initial bubble point (IPA) of the sintered metal filter medium provided in this application is 50-500 kPa. This means that the fine layer in the sintered metal filter medium can effectively trap particles with a diameter of less than 100 nm and has nanometer-scale pores. Considering that the pores of the fine layer porous structure are obtained by sintering the fine layer metal particles as the boundary, the pore size is highly correlated with the particle size of the fine layer raw material metal particles. Therefore, nanometer-scale pores generally also mean that the particle size of the fine layer metal particles is also in the nanometer scale.
[0015] As mentioned earlier, the presence of pinning nodes in nanoscale layers inevitably leads to a wider particle size distribution of the metal particles, resulting in differences in the degree of sintering across different regions. Specifically, the presence of larger pinning nodes means that during the sintering process of the sintered metal filter media, the process of metal particles around the pinning nodes fusing together and forming larger grains through grain boundary migration is delayed, preventing rapid grain growth due to excessively rapid grain boundary migration. This results in a moderately refined grain size and a lower degree of sintering in the layer around the pinning nodes. Conversely, the layer without pinning nodes requires a lower sintering driving force, has a larger specific surface area of metal particles, and a faster diffusion rate, thus exhibiting a larger grain size and a higher degree of sintering. In short, the presence of pinning nodes creates highly sintered regions and less sintered regions within the layer, which inevitably affects stress uniformity and the overall mechanical strength of the layer.
[0016] However, for fine layers sintered from nanoscale metal powders, grain refinement can improve the material's toughness. Smaller grain sizes increase the number of grain boundaries, which can hinder crack propagation, thereby improving the material's fracture toughness. Furthermore, the reduction in high-density dislocations and crack initiation points in fine-grained materials further enhances toughness and resistance to deformation. In other words, moderate grain refinement, i.e., reducing grain size, is beneficial for improving the toughness of the sintered body. Therefore, the high-sintering regions present in the fine layers have greater hardness and become de facto hard regions, while the low-sintering regions near pinned nodes in the fine layers have higher toughness and become de facto soft regions. The alternating arrangement of hard and soft regions forms the porous structure of the fine layers.
[0017] In the post-processing of metal filter media, such as the cutting process, regardless of whether the cutting method involves the rapid rotation of the metal filter media or the rapid rotation of the cutting tool, there will be tangential relative movement at the contact point between the outer surface of the fine layer and the cutting tool. This causes the contact point between the fine layer and the cutting tool to be subjected to a large tangential force. Under the action of the tangential force, the fine layer tends to separate into adjacent circumferential regions.
[0018] Under this trend, if finer metal particles with more uniform particle size are used and the sintering degree of the metal filter medium is appropriately increased, the porous structure of the fine layer will have a high degree of sintering, and the metal particles will form a hard whole through a large number of sintering necks. When the tangential force is applied to a certain area, it will not directly cause the axial adjacent areas to break apart. The porous structure with high integrity will cause the tangential force to be inevitably transmitted axially to the nearby positions, thereby causing the circumferential separation between the blocky porous structures of the fine layer, which manifests as axially extending cracking.
[0019] The fine layer of this application is a special porous structure with small hard and soft regions spaced apart. Therefore, although tangential forces are still inevitably transmitted axially in the hard regions, they are also inevitably transmitted to the soft regions with good toughness and a certain plastic deformation capacity. The soft regions dissipate the tangential forces through a certain amount of plastic deformation, making it difficult for them to be transmitted axially further, and even more so, to tear the next hard region circumferentially. On the other hand, the pinning effect of the pinning nodes themselves hinders the axial transmission of tangential forces, so that the tangential forces must bypass the pinning nodes to reach the next hard region, thereby lengthening the cracking path and naturally increasing the energy required for cracking. Under the influence of multiple factors, crack propagation is suppressed at the microscopic level and does not produce macroscopic cracking phenomena. In addition, if the tangential force is applied directly to the soft area, which is inherently less robust and more susceptible to plastic deformation, the soft area is more likely to break off from the adjacent axial regions. The tangential force is transmitted circumferentially without axial transmission. The axially transmitted tangential force is dissipated within the soft area through plastic deformation, and microcracks may not even begin to form.
[0020] In short, the presence of pinning nodes creates a unique porous structure with alternating hard and soft regions. On one hand, if tangential forces act directly on the soft regions, the plastic deformation of the soft regions reduces the probability of microcrack formation to some extent. On the other hand, if tangential forces act directly on the hard regions, they form the initiation point of microcracks. When the microcracks extend to a certain length and reach the soft regions, the plastic deformation of the soft regions prevents the microcracks from continuing to extend, let alone tearing the next hard region circumferentially. In addition, the hindering effect of the pinning nodes means that the further extension of microcracks must bypass the pinning nodes, which lengthens the cracking path and increases the energy required for cracking. The combination of these factors significantly reduces the probability of cracking in the sintered metal filter medium provided in this application during the cutting operation. During the welding process of the sintered metal filter medium, the temperature at the welding point is high, while the temperature on both sides of the circumference is low. This temperature unevenness leads to different shrinkage and expansion in different areas, thus forming a region of uneven stress in the circumference. This also tends to separate adjacent areas in the circumference. Therefore, the special structure of this application can also reduce the possibility of cracking during the welding process.
[0021] It should be noted that, as mentioned above, local microcracks still exist, but their size is controlled at the micro level; moreover, after the sintered metal filter media is cut, these local microcracks will eventually melt and seal during the subsequent welding process, and will not affect the integrity of the filter element.
[0022] More specifically, in this application, the surface distribution density of pinning nodes is not less than one per 10 square micrometers, which means that there are enough soft regions. The particle size is not less than 0.4 μm and the average particle size is not less than 0.5 μm, which means that it can affect more surrounding metal particles. Therefore, the volume of a single soft region is large enough. The sufficiently large and spaced soft regions not only significantly reduce the probability of microcrack formation and effectively prevent the continued extension of microcracks, but the pinning effect of the pinning nodes themselves also helps to prevent the spread of cracks. Of course, since the metal filter media in this application is intended for high-pressure supercritical fluid filtration and other applications, its mechanical strength must still ensure that it does not break during use. Therefore, the average particle size of the pinned nodes should not exceed 2.6 μm to avoid forming excessively large individual soft areas. The surface distribution density should not exceed 10 per 10 square micrometers, and the area ratio of the pinned nodes should not exceed 85% to avoid an excessive number of soft areas. Too many and excessively large soft areas will inevitably extend continuously rather than be spaced out. While this can indeed further reduce the possibility of cutting and cracking, it is difficult to guarantee that the fine layer has sufficiently high hardness and strength to prevent it from being crushed under high-pressure filtration conditions. That is, a sufficient number of spaced soft areas are needed to prevent axial cracking under tangential forces during post-processing, but a sufficient number of spaced hard areas are also needed to prevent the fine layer porous structure from being crushed due to insufficient self-support capacity under positive pressure.
[0023] The particle size and average particle size of the pinned nodes were obtained as follows: In the SEM image of the outer surface of the fine layer of the sintered metal filter media, any pinned node was randomly selected. Four intersecting line segments were drawn on the surface of each pinned node, with the endpoints of each segment located on the boundary of the pinned node. The included angle between any two adjacent line segments was approximately 45°. The length of each line segment was measured using software such as NanoMeasure. The average length of the four line segments was taken as the particle size of the pinned node. Furthermore, the average particle size of the pinned nodes was obtained by averaging the particle sizes of any 20 or more pinned nodes.
[0024] The areal distribution density of pinned nodes is obtained by counting the number of pinned nodes in the entire field of view of the SEM image of the outer surface of the fine layer of the sintered metal filter medium, and then dividing the counted number by the area of the corresponding field of view to obtain the areal distribution density of pinned nodes.
[0025] The area ratio of pinned nodes is calculated as follows: Calculate the sum of the areas of all pinned nodes in the SEM image of the outer surface of the fine layer of the sintered metal filter medium, for example, 20μm*20μm, 30μm*30μm, or the entire field of view. Then, divide the sum of the areas of all pinned nodes by the area of the corresponding field of view to obtain the area ratio of the pinned nodes. In this case, a single pinned node is approximated as a circle, and the area of each pinned node is approximately calculated. The sum of the areas of all pinned nodes is the sum of the areas of all pinned nodes.
[0026] Preferably, the average particle size of the pinning nodes is 0.6-2 μm, and the surface distribution density of the pinning nodes is 2-7 per 10 square micrometers.
[0027] More preferably, the average particle size of the pinning nodes is 0.7-2 μm.
[0028] When the average grain size of the pinned nodes decreases, the pinned nodes themselves weaken their resistance to the axial propagation of microcracks, and the corresponding soft zone becomes smaller. The resistance of the soft zone to the axial propagation of microcracks also weakens, but it helps to improve the uniformity of stress distribution in the fine layers. Conversely, when the average grain size of the pinned nodes increases, the pinned nodes themselves strengthen their resistance to the axial propagation of microcracks, and the corresponding soft zone becomes larger. The resistance of the soft zone to the axial propagation of microcracks also strengthens, but it exacerbates the non-uniformity of stress distribution in the fine layers. When the surface distribution density of pinned nodes decreases, the pinned nodes are more sparsely distributed in the porous structure of the fine layers, the number of soft regions is also less, the probability of microcrack formation is relatively higher, and the probability of microcracks being hindered during axial propagation is also reduced. Conversely, when the surface distribution density of pinned nodes increases, the pinned nodes are more densely distributed in the porous structure of the fine layers, the number of soft regions is also more, the probability of microcrack formation is relatively lower, and the probability of microcracks being hindered during axial propagation is also increased.
[0029] Therefore, when pinning nodes with relatively smaller average particle size are used, their surface distribution density can be increased simultaneously. That is, when the particle size of the pinning nodes and the volume of the soft zone are small, the hindrance and interception effect of a single pinning node and a single soft zone on the axial extension of microcracks is relatively weaker. Appropriately increasing the number of pinning nodes and soft zones is beneficial to reducing the probability of microcrack formation during cutting and increasing the probability of hindrance when microcracks propagate axially, thereby making the sintered metal filter medium have a lower probability of cutting cracking.
[0030] When pinning nodes with relatively larger average particle size are used, their surface distribution density can be reduced simultaneously. That is, when the particle size of the pinning node and the volume of the soft zone are larger, the single pinning node and the single soft zone have a stronger effect on hindering and intercepting the axial extension of microcracks. Appropriately reducing their number can improve the uniformity of stress distribution of sintered metal filter media, increase its hardness and strength, and thus improve its mechanical stability under high pressure filtration conditions.
[0031] Specifically, when the average particle size of the pinned nodes is set to be no less than 0.6 μm, the minimum average particle size of the pinned nodes is increased. Pinned nodes with a relatively larger minimum average particle size will exacerbate the stress inhomogeneity of the fine layer. At the same time, setting the surface distribution density of the pinned nodes to no more than 7 per 10 square micrometers and appropriately reducing the maximum surface distribution density of the pinned nodes will correspondingly reduce the maximum number of soft zones. That is, pinned nodes with a relatively larger minimum average particle size, combined with a slightly lower maximum surface distribution density, can improve the stress distribution uniformity of the sintered metal filter media. To improve uniformity, enhance strength and hardness, thereby improving mechanical stability under high-pressure filtration conditions; simultaneously, increase the surface distribution density to no less than 2 per 10 square micrometers, appropriately increase the minimum surface distribution density of pinned nodes, and correspondingly increase the minimum number of soft zones. That is, the pinned nodes with a relatively larger minimum average particle size, combined with a slightly larger minimum surface distribution density, can reduce the probability of microcrack formation during cutting and increase the probability of axial propagation of microcracks being hindered, thus making the cracking probability of sintered metal filter media lower during cutting.
[0032] When the average particle size of the pinned nodes is set to no more than 2 μm, the maximum value of the average particle size of the pinned nodes is reduced. Pinned nodes with a relatively smaller maximum average particle size improve the stress uniformity of the fine layer. At the same time, by increasing the surface distribution density of the pinned nodes to no less than 2 per 10 square micrometers and appropriately increasing the minimum value of the surface distribution density of the pinned nodes, the minimum number of soft zones is also increased accordingly. That is, pinned nodes with a relatively smaller maximum average particle size combined with a larger minimum surface distribution density can reduce the probability of microcrack formation during cutting and increase the probability of axial propagation of microcracks being hindered, thus making the probability of cutting cracks in sintered metal filter media lower. Meanwhile, increasing its surface distribution density to no more than 7 per 10 square micrometers and appropriately reducing the maximum value of the surface distribution density of the pinned nodes also reduces the maximum number of soft zones. That is, pinned nodes with a relatively smaller maximum average particle size combined with a smaller maximum surface distribution density can improve the stress distribution uniformity of the fine layer, increase its strength and hardness, and improve its mechanical stability under high-pressure filtration conditions.
[0033] Preferably, the pinning nodes include at least a first pinning node with a particle size of 0.5-1.5 μm and a second pinning node with a particle size greater than 1.5 μm, and the number of the first pinning nodes accounts for 30-90%.
[0034] The first pinning node has a smaller grain size and a smaller corresponding soft region volume, which helps improve the uniformity of stress distribution in the fine layer. However, the first pinning node and its corresponding soft region have a weaker resistance to the axial propagation of microcracks. On the other hand, the second pinning node has a larger grain size and a larger corresponding soft region volume. The second pinning node and its corresponding soft region have a stronger resistance to the axial propagation of microcracks, but at the same time, they exacerbate the non-uniformity of stress distribution in the fine layer.
[0035] If the number of first-stage pinning nodes is too high and their particle size is relatively small (i.e., too many small pinning nodes), the number of small soft areas will also be too high, reducing the resistance to axial propagation of microcracks. Conversely, if the number of second-stage pinning nodes is too high and their particle size is relatively large, in order to ensure that the fine layer has sufficiently high hardness and strength to guarantee its mechanical stability under high-pressure filtration conditions, the surface distribution density of the pinning nodes in the porous structure of the fine layer must be reduced. That is, the pinning nodes will be more sparsely distributed in the porous structure of the fine layer, meaning the spacing between any adjacent pinning nodes will be larger. Consequently, the probability of microcrack formation during the cutting process of the sintered metal filter medium will increase, while the probability of resistance to axial propagation of microcracks will decrease.
[0036] In this application, the proportion of first pinning nodes with a particle size of 0.5-1.5μm is set to 30-90%, and correspondingly, the proportion of second pinning nodes with a particle size greater than 1.5μm is 10-70%, with the proportion of second pinning nodes not less than 10%. The particle size and number of the first and second pinning nodes are both appropriate, with the particle size not too large or too small, and the number not too many or too few. The first and second pinning nodes work together to ensure that a certain number of second pinning nodes and corresponding soft areas provide sufficiently strong resistance to the axial propagation of microcracks, while a sufficient number of first pinning nodes and corresponding soft areas improve the uniformity of stress distribution in the fine layer, reduce the probability of microcrack formation, and increase the probability of resistance to the axial propagation of microcracks, thereby further reducing the probability of cutting and cracking of the sintered metal filter media.
[0037] More preferably, the second pinning node includes a break-resistant node with a particle size of not less than 3 μm, and the number of the break-resistant nodes does not exceed 10% of the total number of pinning nodes and is not less than 3% of the total number of pinning nodes.
[0038] The particle size of the crack-resistant nodes is not less than 3μm, meaning their particle size is relatively large, and the corresponding soft zone volume is also relatively large. The crack-resistant nodes and their corresponding soft zones exert a stronger resistance to the axial propagation of microcracks, enabling the axial size of microcracks to be controlled to be smaller. Therefore, the presence of a small number of crack-resistant nodes helps reduce the probability of cutting and cracking in the sintered metal filter media. However, precisely because the particle size of the crack-resistant nodes is relatively large, the stress non-uniformity of their corresponding soft zones is more severe. If their content is too high, it may affect the mechanical stability of the sintered metal filter media under high-pressure filtration conditions; therefore, the amount of these crack-resistant nodes should not be excessive.
[0039] Specifically, in this application, when the proportion of the above-mentioned crack-blocking nodes is controlled to be no less than 3%, the probability of cutting and cracking of the sintered metal filter medium is reduced by using an appropriate number of crack-blocking nodes and corresponding soft areas. When the proportion of the number of crack-blocking nodes is controlled to be no more than 10%, the mechanical stability of the sintered metal filter medium under high pressure filtration conditions is guaranteed.
[0040] Preferably, the average shape factor of the pinned nodes is not greater than 1.15.
[0041] The average shape factor is obtained as follows: Select any pinned node from the SEM image of the outer surface of the sintered metal filter medium. Draw four intersecting line segments inside each pinned node. The intersection of these line segments represents the approximate geometric center of the pinned node. The start and end points of each line segment are the intersections with the edge of the pinned node. The angle between any two adjacent line segments is approximately 45 degrees. Measure the length of each line segment using software such as NanoMeasure. Calculate the ratio of the difference between the maximum and minimum lengths of the four line segments to the average length. This ratio is taken as the shape factor of the pinned node. At least 10 pinned nodes are selected in the same manner, and the shape factor of each node is calculated. The average shape factor is then obtained by averaging these values.
[0042] When the average shape factor of the pinned nodes is no greater than 1.15, for example, when the major and minor axes of the pinned nodes are 3 and 1 respectively, meaning that the dimensions of the pinned nodes in all directions do not differ significantly, the shape of the pinned nodes is similar to an ellipsoid or sphere. Their specific surface area is relatively small, resulting in slower heat absorption. During sintering, the degree of sintering of the fine particles at and near the pinned nodes decreases, the grain growth rate of the fine particles in the fine layers slows down, the grains are refined, and the toughness of the corresponding soft region improves. Therefore, when tangential forces act directly on the soft region, the better plastic deformation capacity of the soft region can further reduce the probability of microcrack formation; when tangential forces act on the hard region, and microcracks extend to the soft region, the better plastic deformation capacity of the soft region can better suppress the axial propagation of microcracks, meaning it has a stronger hindering effect on the axial propagation of microcracks.
[0043] More preferably, the pinning nodes include spheroidal nodes with a shape factor of not more than 0.7, and the number of spheroidal nodes accounts for not less than 60%.
[0044] The smaller the shape factor, the higher the uniformity of the dimensions of the pinned nodes in all directions, and the closer their shape is to a sphere. Pinned nodes with a shape factor of no more than 0.7 are defined as spheroidal nodes, and their corresponding soft regions have higher toughness. Spheroidal nodes and their corresponding soft regions can reduce the probability of microcrack formation and have a stronger resistance to the axial propagation of microcracks. However, because spheroidal nodes are close to spherical in shape, they absorb heat slowly during sintering, which will significantly reduce the sintering degree of the corresponding soft regions, thereby reducing the overall sintering integrity of the fine layers.
[0045] In this invention, the number of spherical nodes with a shape factor of no more than 0.7 accounts for no less than 60%, ensuring that there are enough soft areas with high toughness, which can significantly reduce the probability of microcrack formation and the probability of microcracks further propagating axially, thereby reducing the probability of sintered metal filter media being cut and cracked.
[0046] Preferably, the average distance between two adjacent pinning nodes is 0.2-2 μm.
[0047] In this context, two adjacent pinning nodes refer to two pinning nodes that have no other pinning nodes between them. The minimum distance between the edges of these two adjacent pinning nodes is taken as the spacing between them. At least 10 sets of adjacent pinning nodes are randomly selected from the SEM image of the outer surface of the sintered metal filter medium. The spacing between these 10 sets of adjacent pinning nodes is measured using measurement software such as NanoMeasure, and the average of these 10 spacings is taken as the average spacing between adjacent pinning nodes.
[0048] The average spacing between two adjacent pinning nodes is not less than 0.2 μm, and the surface distribution density of pinning nodes in the porous structure of the fine layer does not exceed 10 per 10 square micrometers. This can prevent soft areas from merging into one in the fine layer, improve the uniformity of its stress distribution, and ensure that the fine layer has sufficiently high strength and hardness to guarantee the mechanical stability of the sintered metal filter media under high pressure filtration conditions.
[0049] Provided that the surface distribution density of pinning nodes in the porous structure of the fine layer is not less than one per 10 square micrometers, further controlling the average spacing between two adjacent pinning nodes to not more than 2 μm can reduce the probability of microcrack formation and reduce the possibility of microcracks passing through the two pinning nodes when propagating axially, thereby achieving the goal of reducing the probability of cracking of sintered metal filter media during the cutting process.
[0050] More preferably, the sintered metal filter medium further includes a coarse layer located radially inside the fine layer, the coarse layer having a porous structure, and the coarse layer and the fine layer being sintered together; or, the sintered metal filter medium further includes a coarse layer located radially inside the fine layer and at least one functional layer located radially inside the coarse layer, the coarse layer and the functional layer both having porous structures, the functional layer, the coarse layer, and the fine layer being sintered together, and the functional layer being at least one of a pre-filtration layer, a reinforcing layer, and a separation layer.
[0051] The porous metal membrane element disclosed in the aforementioned USRE36249E1 has a relatively uniform overall pore size and porosity. However, the process gas to be treated may contain both large-diameter and small-diameter particulate pollutants. In order to ensure the retention capacity of small-diameter pollutants, the pore size of the porous metal membrane element should not be too large. This results in the relatively concentrated retention of particulate pollutants of various sizes in a certain area. Therefore, the porous metal membrane element often experiences the problem of local pores being concentrated and quickly blocked by particulate pollutants of different sizes during use, leading to a short service life of the filtration device.
[0052] The sintered metal filter medium of the present invention can be a two-layer porous structure or a three-layer or more porous structure. When the sintered metal filter medium has a two-layer porous structure, the surface of the coarse layer facing away from the fine layer is the inner surface of the sintered metal filter medium. The coarse layer is formed by sintering metal particles with larger particle sizes, and has a larger pore size. Therefore, the coarse layer acts as a pre-filtration layer, trapping large-sized particulate impurities, while the fine layer with smaller pore sizes traps small-sized particulate impurities. The coarse and fine layers work together to achieve efficient regional trapping of particulate impurities of various sizes. At the same time, this non-centralized trapping structure also improves the overall dirt-holding capacity of the sintered metal filter medium and avoids the possibility of concentrated and rapid clogging. In addition, the sintered neck size formed by the metal particles in the coarse layer is larger, and the bonding strength between particles is higher. Therefore, the coarse layer also plays a role in supporting and strengthening the fine layer to improve the overall mechanical strength of the sintered metal filter medium.
[0053] When the sintered metal filter medium has a porous structure of 3 or more layers, at least one functional layer is integrally sintered on the surface of the coarse layer away from the fine layer. The functional layer is at least one of the pre-filtration layer, reinforcing layer, and separation layer, and can also play the roles of pre-filtration and support.
[0054] Preferably, when the surface of the coarse layer facing away from the fine layer is the inner surface of the sintered metal filter medium, the pore area ratio of the surface of the coarse layer facing away from the fine layer is 10-40%.
[0055] The porosity can be measured by the following method: import the SEM image of the inner surface of the sintered metal filter medium into image processing software such as ImageJ, and use the software to calculate the sum of the areas of all pores on the inner surface and the total area of the inner surface. The ratio of the sum of the areas of all pores to the total area of the inner surface is the porosity.
[0056] The pore area ratio on the surface of the coarse layer facing away from the fine layer is controlled to not exceed 40%, ensuring a sufficiently high degree of sintering of the coarse layer to guarantee its mechanical strength. This allows the coarse layer to effectively support the fine layer, improving the overall mechanical strength of the sintered metal filter medium. Consequently, the coarse layer achieves a sufficiently high retention efficiency and ensures a certain flow rate for adequate pre-filtration. Simultaneously, the pore area ratio on the surface of the coarse layer facing away from the fine layer is controlled to be no less than 10%, ensuring that the coarse layer itself has sufficient porosity to reduce flow resistance. This, in turn, ensures that both the coarse layer and the sintered metal filter medium as a whole have a sufficiently high flow rate.
[0057] Preferably, the average width of the sintering neck on the side of the coarse layer facing away from the fine layer is 0.2-6 μm, the average maximum Fret diameter of the pores is 0.5-7 μm, and the ratio of the maximum Fret diameter to the minimum Fret diameter of the pores is 1.2-5.
[0058] The sintering neck of the coarse layer refers to the fused portion formed by coarse particles during sintering, while the pores are the areas enclosed by the boundaries of the coarse particles. The average width of the sintering neck, and the maximum and minimum Fret diameters of the pores, can be obtained through the following methods: SEM images of the inner surface of the sintered metal filter media are imported into measurement software such as NanoMeasure. The width of at least 10 sintered necks is measured, and the average of these 10 widths is taken as the average width of the sintered neck. SEM images of the inner surfaces of at least 10 sintered metal filter media products are imported into image processing software such as ImageJ. The maximum and minimum Frett diameters of the pores in the SEM images of each product are measured. The average of the 10 maximum Frett diameters is then calculated to obtain the average maximum Frett diameter of the pores. The ratio of the maximum Frett diameter to the minimum Frett diameter of the pores is then calculated.
[0059] The average width of the sintering neck of the coarse layer is controlled to be no less than 0.2 μm, the average maximum Fret diameter of the pores is no greater than 7 μm, and the ratio of the maximum Fret diameter to the minimum Fret diameter of the pores is no more than 5. This ensures that the coarse particles of the coarse layer are fully sintered, so that the mechanical strength of the coarse layer itself is high enough to better support the fine layer. The pore size of the coarse layer is not too large, and the dimensional differences in all directions of the pores are not too large. That is, the shape of the pores is relatively regular, so that the coarse layer can provide a better pre-filtration effect.
[0060] Further control is made to ensure that the average width of the sintered neck of the coarse layer is no greater than 6 μm, the average maximum Fret diameter of the pores is no less than 0.5 μm, and the ratio of the maximum Fret diameter to the minimum Fret diameter of the pores is no less than 1.2. This is to avoid the pore blockage of the coarse layer due to excessive sintering of coarse particles, so that the coarse layer has enough large pores and better uniformity of the pore size in all directions, so as to ensure that the coarse layer and the sintered metal filter media can provide a high flux.
[0061] Preferably, the thickness of the sintered metal filter medium is 120-3000 μm, and the thickness of the fine layer is 1 / 6-2 / 3 of the thickness of the sintered metal filter medium.
[0062] First, the overall thickness of the sintered metal filter medium is no less than 120 μm, and the thickness of the fine layer is no less than 1 / 6 of the overall thickness of the sintered metal filter medium, i.e., the thickness of the fine layer is no less than 20 μm. This ensures that the sintered metal filter medium itself is thick enough to have sufficiently high mechanical strength to withstand the high pressure differential under filtration conditions, and to have a sufficiently large dirt holding capacity and a relatively long service life. At the same time, the fine layer is also thick enough to allow the pinning nodes to be evenly dispersed in the fine layer and fully fused with the fine particles, ensuring the sintering integrity of the fine layer and the overall sintered metal filter medium, as well as ensuring the retention efficiency and dirt holding capacity of the fine layer. Second, the overall thickness of the sintered metal filter medium is no greater than 3000 μm, and the thickness of the fine layer is no greater than 2 / 3 of the overall thickness of the sintered metal filter medium, i.e., the thickness of the fine layer is no greater than 2000 μm. This avoids excessive thickness of the sintered metal filter medium and the fine layer, which would result in excessive flow resistance and lead to a low filtration flux.
[0063] Preferably, the porosity of the sintered metal filter medium is 20-40%.
[0064] The porosity of the sintered metal filter media was measured by the water displacement method. The specific operating steps are as follows: First, the apparent volume V0 of the sintered metal filter medium is calculated from the inner and outer diameters and axial height of the hollow tubular sintered metal filter medium. Then, the hollow tubular sintered metal filter medium is completely immersed in water of volume V1, and a vacuum is applied for 30 minutes to ensure that the water completely fills the pores of the hollow tubular sintered metal filter medium. The total volume V2 of water immersing the hollow tubular sintered metal filter medium is then recorded. Therefore, the porosity of the sintered metal filter medium is... .
[0065] The porosity of sintered metal filter media is not less than 20%, which can provide a larger flow rate and better retention effect, while the porosity of sintered metal filter media is not greater than 40%, ensuring that it is fully sintered to guarantee that it has higher strength and hardness.
[0066] Preferably, the fine layer is formed by sintering a mixture, the mixture comprising at least fine particles and doped particles, the doped particles forming pinning nodes of the porous structure of the fine layer, and the particle size of the doped particles being larger than that of the fine particles.
[0067] A second aspect of the present invention also provides a method for preparing the sintered metal filter medium, comprising the following steps: S1: A mixture is provided, the mixture being composed of fine particles and doped particles uniformly dispersed therein, and the mixture is compressed to obtain a hollow tubular green embryo, the mixture being prepared by the following steps: A1 - A mixed precursor is obtained by mixing a dispersant with a surface tension of not more than 30 mN / m with fine particles and doped particles, wherein the particle size of the fine particles is 50-300 nm, the particle size of the doped particles is not less than 0.4 μm and the average particle size is 0.5-2.6 μm, and the mass of the doped particles is 15-85% of the total mass of the fine particles and the doped particles; A2 - Allow the mixed precursor to stand, then sonicate the mixed precursor to obtain a dispersed precursor; A3 - Stir and heat the dispersion precursor, then dry to obtain a mixture; S2: The green blank obtained by sintering S1 yields a pre-finished sintered metal filter medium. S3: Cut at least one end of the sintered metal filter media pre-product obtained in S2 to obtain the sintered metal filter media.
[0068] In step A1, by controlling the particle size of the doped particles to be not less than 0.4 μm and the average particle size to be 0.5-2.6 μm, and the mass of the doped particles to be 15-85% of the total mass of the fine particles and the doped particles, the particle size of the pinned nodes in the sintered fine layer and their surface distribution density in the porous structure of the fine layer can be controlled within the range of this invention. A dispersant with a surface tension not greater than 30 mN / m is mixed with the fine particles and the doped particles to obtain a mixing precursor. This dispersant has low surface tension and good wetting properties, which is beneficial for the uniform mixing of the doped particles and the fine particles, better wetting the surface of all particles, effectively preventing the formation of agglomerates of nanoscale fine particles during the mixing process, and initially dispersing the agglomerates of fine particles, thereby reducing the difficulty and energy consumption of step A2. More preferably, the mass of the doped particles is 30-85% of the total mass of the fine particles and the doped particles.
[0069] In step A2, during the settling of the mixing precursor, the fine particle agglomerates and doped particles will deposit at the bottom of the mixing precursor. By setting the mass of the doped particles to 15-85% of the total mass of the fine particles and doped particles, the doped particle content is high enough that after the mixing precursor has been set, the fine particle agglomerates and doped particles are distributed at intervals at the bottom of the mixing precursor. The probability of doped particles being dispersed around the agglomerates is relatively high. When the settling mixing precursor is ultrasonically treated, the fine particle agglomerates are not only impacted by ultrasonic waves but also by the doped particles. During the impact or collision process, once small gaps are formed between the fine particles, the dispersant with a surface tension of less than 30 mN / m can quickly penetrate into the gaps. The surface of the fine particles in the not-yet-fully-dispersed agglomerates is gradually wetted, accelerating the speed at which the agglomerates are completely dispersed. The surface of the dispersed fine particles is fully wetted by the dispersant, so that agglomerates will not form again. Finally, a dispersed precursor in which the fine particle agglomerates are completely dispersed is obtained.
[0070] It should be noted that it is generally believed that the static setting operation not only fails to improve the dispersion effect, but also leads to the separation of particles of different sizes. However, this application combines the static setting operation with the ultrasonic operation to achieve the dispersion of agglomerates of nanoscale particles. That is, the static setting operation, which is generally used for material separation, is used for the dispersion of agglomerates of fine powder, thus broadening the application scope of the static setting operation.
[0071] Since the doped particles in the dispersion precursor obtained in step A2 are basically at the bottom of the dispersion precursor and have not yet been uniformly dispersed in the fine particles, step A3 is further performed to stir and heat the dispersion precursor obtained in step A2. The stirring is to uniformly disperse the doped particles into the fine particles, while heating is performed at the same time to evaporate the dispersant, thereby solidifying the dispersion of the doped particles in the fine particles and preventing the doped particles that are uniformly dispersed in the fine particles from depositing back to the bottom of the dispersion precursor, thus obtaining a dry mixture in which the doped particles are uniformly dispersed in the fine particles.
[0072] The mixture obtained in step A3 is then compressed to obtain a hollow tubular green preform, thus completing step S1 and obtaining the green preform to be sintered. Step S2 is then performed to sinter the green preform obtained in step S1 to obtain a sintered metal filter medium pre-product; finally, step S3 is performed to cut at least one end of the sintered metal filter medium pre-product obtained in step S2 to obtain the sintered metal filter medium.
[0073] It should be noted that the sintered metal filter medium of this application can be a two-layer porous structure or a three-layer or more porous structure. Therefore, step S1 can provide porous raw materials according to the overall structure of the sintered metal filter medium. For example, when the sintered metal filter medium also includes a coarse layer located radially inside the fine layer, step S1 can also provide coarse particles with a particle size of 1-10 μm. During the pressing of the green body, the mixture is located radially outside the coarse particles. The coarse particles and the mixture are compressed to obtain a hollow tubular green body. Then, steps S2 and S3 are executed sequentially to obtain the sintered metal filter medium.
[0074] Steps A1, A2, and A3 work together to obtain the above-mentioned dry mixture, in which the doped particles are uniformly dispersed in the fine particles. Furthermore, since the mixture and coarse particles are fully pressed to obtain a green embryo before sintering, a certain amount of contact and compression are formed between the particles, which further solidifies the dispersion of the doped particles in the fine particles. Therefore, during the sintering process, the dispersion state of the doped particles in the fine particles remains basically unchanged, maintaining the uniform dispersion state of the particles in the mixture before pressing. Correspondingly, after sintering, the coarse particles sinter to form a coarse layer porous structure, the mixture forms a fine layer porous structure, and the doped particles form pinned nodes in the fine layer porous structure. Correspondingly, the dispersion state of the pinned nodes in the fine layer porous structure is similar to that of the doped particles in the mixture. Moreover, since the particle size of the doped particles is relatively large, the heat absorption is slow during sintering, the deformation is small and negligible, and the particle size remains basically unchanged. Thus, in the sintered metal filter medium, the particle size of the pinned nodes is still not less than 0.4 μm, and the average particle size is 0.5-2.6 μm. The surface distribution density of the pinned nodes in the fine layer porous structure is 1-10 per square micrometer, and the area ratio of the pinned nodes does not exceed 85%. In addition, since the particle size of the fine particles is 50-300nm, the pore size of the fine layer is also on the nanometer scale, so the initial bubble point of the IPA of the sintered metal filter media is 50-500kPa.
[0075] It should be noted that in the preparation process of the sintered metal filter medium provided in this application, before sintering, doped particles of the corresponding particle size are uniformly dispersed in fine particles at a certain mass ratio to form a mixture. The mixture is then compressed to obtain a hollow tubular green body, which is further sintered to obtain a porous structure of fine layers. The pinning nodes are dispersed in the porous structure of the fine layers with a corresponding areal density. The uniform dispersion of doped particles in the fine particles is a key step, directly determining the dispersion state of the pinning nodes in the porous structure of the fine layers after sintering. Therefore, other processes such as spraying and filtration are not suitable for the preparation of this sintered metal filter medium because these processes often result in the separation of large doped particles from the fine particles, failing to guarantee uniform dispersion of the doped particles in the fine particles. Consequently, the pinning nodes in the resulting porous structure of the fine layers are not uniformly dispersed.
[0076] Preferably, step A2 is repeated 2-4 times; and / or, in step A2, the settling time is 30-90 minutes, the ultrasonic power is 100-300W, and the ultrasonic time is 3-15 minutes.
[0077] The mixed precursor should be subjected to at least two settling and ultrasonic operations to ensure that the agglomerates of fine particles in the mixed precursor are completely dispersed, which is conducive to the full sintering of fine particles and avoids the appearance of unsintered fine particles; and the mixed precursor should be subjected to a maximum of four settling and ultrasonic operations to avoid the doped particles being broken or damaged, resulting in irregular shapes, which is not conducive to the formation of soft areas or leads to a decrease in the toughness of soft areas.
[0078] The settling time for the mixing precursor should be at least 30 minutes. Correspondingly, after one settling operation, more fine particle agglomerates and dopants separate from the fine particles and deposit at the bottom of the mixing precursor. In a subsequent ultrasonic operation, a large number of fine particle agglomerates will be dispersed, thereby improving the efficiency of a single ultrasonic dispersion and reducing the number of settling and ultrasonic operations. If the settling time is less than 30 minutes, due to the relatively short settling time, it may be necessary to increase the number of settling and ultrasonic operations to fully disperse the fine particle agglomerates. When the settling time of the mixing precursor reaches 90 minutes, the amount of fine particle agglomerates and dopants separated from the fine particles is close to its maximum. Further extending the settling time will not significantly increase the amount of fine particle agglomerates and dopants deposited at the bottom of the mixing precursor. Therefore, it is unnecessary to set the settling time to more than 90 minutes, and it is also not conducive to improving the dispersion efficiency of the mixing precursor.
[0079] Based on this, the settling time is controlled between 30 and 90 minutes, which improves the dispersion efficiency while ensuring that the fine particle agglomerates are dispersed evenly and fully.
[0080] To ensure that the fine particle aggregates can be dispersed quickly and fully, the ultrasonic power should not be less than 100W during the ultrasonic operation, and the ultrasonic time should not be less than 3 minutes. At the same time, to avoid damage to the doped particles by prolonged impact of excessively high-power ultrasonic waves, the ultrasonic power should not exceed 300W and the ultrasonic time should not exceed 15 minutes.
[0081] The mixed precursor undergoes at least two settling and ultrasonic operations, with each settling time not less than 30 minutes and each ultrasonic operation having a power of not less than 100W and an ultrasonic time of not less than 3 minutes, to achieve sufficient and efficient dispersion of fine particle agglomerates. At the same time, the mixed precursor undergoes at most four settling and ultrasonic operations, with each settling time not exceeding 90 minutes and each ultrasonic operation having a power of not more than 300W and an ultrasonic time of not more than 15 minutes, to improve dispersion efficiency while achieving sufficient dispersion of fine particle agglomerates and avoiding damage to doped particles, so as to ensure that they play an effective pinning role during sintering, thereby improving the toughness of soft areas.
[0082] Preferably, the fine particles and doped particles are made of stainless steel, and the coarse particles are made of nickel or nickel carbonyl. In step S2, the sintering process includes a heating stage and a subsequent holding stage. The heating stage involves uniformly increasing the ambient temperature to 780-820°C at a rate of 2-8°C / min, and the holding stage involves holding at 780-820°C for 20-40 minutes.
[0083] The heating rate during the warming stage should not be too fast. That is, during the process of the green body rising from ambient temperature to the holding temperature, the heating rate should not be too rapid. Otherwise, when the temperature reaches the holding temperature, the temperature difference between the coarse particles and the mixture will be too large, leading to an excessive difference in sintering shrinkage rates between the coarse particles and the mixture during the holding stage. Ultimately, this results in interlayer cracking between the porous structures of the coarse and fine layers, meaning that the porous structures of the coarse and fine layers fail to form effective fusion at the interface. Of course, a slower heating rate is also not better. If the heating rate is too slow, it will lead to low sintering efficiency.
[0084] The choice of holding time during the heat preservation stage affects the sintering effect. If the holding time is too short, the coarse particles absorb too little heat and melt insufficiently, failing to form a sufficient fusion between them. This results in a narrow sintering neck, which also prevents sufficient fusion between fine particles and between fine particles and doped particles. Consequently, the strength and hardness of the resulting sintered metal filter medium are poor, making it unable to withstand high pressure differential filtration conditions. On the other hand, if the holding time is too long, both coarse and fine particles are severely over-sintered, leading to pore blockage in both the coarse and fine layers. Consequently, the porosity and pore size of the sintered metal filter medium are very low, resulting in high flow resistance and a very low flux during filtration.
[0085] Specifically, in this application, the fine and doped particles of the mixture are made of stainless steel, the coarse particles are made of nickel or nickel carbonyl, and the coarse particles have a particle size of 1-10 μm, the fine particles have a particle size of 50-300 nm, the doped particles have a particle size of not less than 0.4 μm and an average particle size of 0.5-2.6 μm, and the mass of the doped particles is 15-85% of the total mass of the fine and doped particles. The green body is further heated uniformly from room temperature (e.g., 25 °C) to a holding temperature of not less than 780 °C at a heating rate of not less than 2 °C / min, and held at this holding temperature for at least 20 min; or, the green body is heated uniformly from room temperature (e.g., 25 °C) to a holding temperature of not more than 820 °C at a heating rate of not less than 2 °C / min, and held at this holding temperature for no more than 40 min; or, the green body is heated uniformly from room temperature (e.g., 25 °C) to a holding temperature of not more than 820 °C at a heating rate of not more than 8 °C / min. The heating rate is uniformly increased from room temperature (e.g., 25°C) to a holding temperature of not less than 780°C, and held at this holding temperature for at least 20 minutes; or, the green compact is uniformly heated from room temperature (e.g., 25°C) to a holding temperature of not more than 8°C / min at a heating rate of not more than 8°C / min, and held at this holding temperature for no more than 40 minutes. In this way, when the green compact reaches the holding temperature through the heating stage, the temperature of the coarse particles and the mixture is basically uniform, and the holding time of the holding stage is reasonable, neither too long nor too short. Effective fusion is formed between coarse particles, between fine particles, and between fine particles and doped particles, and effective fusion is also formed at the interface between the coarse and fine layers. There is no problem of pore blockage in the coarse layer or pore blockage in the fine layer. Thus, a sintered metal filter medium pre-finished product with sufficient sintering and uniform pore structure is obtained, and the sintering efficiency is also relatively high.
[0086] Preferably, in step A1, the dispersant is selected from one or more of methanol, ethanol, n-propanol, isopropanol or n-butanol, and the liquid-to-solid volume ratio in the mixed precursor is 2:1-8:1.
[0087] Methanol, ethanol, n-propanol, isopropanol, or n-butanol have low surface tension and are effective in the initial dispersion of fine particle agglomerates in mixed precursors. In addition, these solvents are relatively common and inexpensive.
[0088] One or more of methanol, ethanol, n-propanol, isopropanol, or n-butanol are used as dispersants, ensuring that the liquid-to-solid volume ratio in the mixed precursor is not less than 2:1, i.e., the volume ratio of the dispersant to the total volume of fine particles and doped particles is not less than 2. The amount of dispersant is sufficient to facilitate the mixing of fine particles and doped particles, fully wet the surface of all particles, and ensure that the dispersant has a good initial dispersion effect on the agglomerates of fine particles. At the same time, the liquid-to-solid volume ratio in the mixed precursor is not greater than 8:1. While ensuring the initial dispersion effect of the agglomerates of fine particles, the amount of dispersant used is minimized to facilitate the rapid removal of the dispersant in the subsequent process.
[0089] Preferably, in step A3, before heating and stirring, the clear dispersant liquid above the dispersion precursor is removed. The stirring rate is 300-600 r / min, the vacuum degree during stirring is 0.02-0.06 MPa, and the temperature is 60-80℃.
[0090] Before heating and stirring, the dispersant liquid above the dispersion precursor is removed. This allows for the rapid removal of more dispersant in the shortest time, significantly shortening the removal time. After the dispersant liquid above the dispersion precursor is removed, the stirring speed is further controlled to be no less than 300 r / min, with a vacuum degree of no less than 0.02 MPa and a temperature of no less than 60°C; or, the stirring speed is controlled to be no more than 600 r / min, with a vacuum degree of no more than 0.06 MPa and a temperature of no more than 80°C. This ensures that the stirring speed matches the heating and evaporation rate of the dispersant, so that when the dopant particles are uniformly dispersed in the fine particles, the dispersant is also completely evaporated. This better solidifies the dispersion of the dopant particles in the fine particles, further improving the uniformity of the dopant particle dispersion in the fine particles, and consequently improving the uniformity of the pinned nodes in the porous structure of the fine layers.
[0091] A third aspect of the present invention also provides a filter element comprising the sintered metal filter medium described above.
[0092] In a fourth aspect, the present invention also provides a method for filtering supercritical carbon dioxide, wherein supercritical carbon dioxide is passed through the sintered metal filter medium during filtration. Attached Figure Description
[0093] To more clearly illustrate the technical solutions in the embodiments of this application or the conventional technology, the drawings used in the description of the embodiments or the conventional technology will be briefly introduced below. Obviously, the drawings described below are only some embodiments of this application. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.
[0094] Figure 1 This is a schematic diagram of the SEM image of the outer surface of the sintered metal filter media product of this application; Figure 2 This is a schematic diagram of the SEM image of the inner surface of the sintered metal filter media product of this application; Figure 3 This is a schematic diagram of the filter element structure of this application; Figure 4 This is a schematic diagram of the structure of the filter in this application.
[0095] Figure 3-4In the middle, 100-filter element, 10-sintered metal filter medium, 20-end plate, 30-connector component, 31-hollow channel, 200-outer shell, 210-connector. Detailed Implementation
[0096] The present application will be further described below through specific preparation examples, embodiments and comparative examples. Preparation example of the mixture Preparation Example 1
[0097] Step A1: Mix fine particles with a particle size of 50-150 nm and an average particle size of 100 nm with doped particles with an average particle size of 1.95 μm to obtain mixed metal particles. Mix the mixed metal particles with the dispersant isopropanol to obtain a mixed precursor. The liquid to solid volume ratio in the mixed precursor is 2:1.
[0098] The particle size distribution of the doped particles is as follows: the first doped particles have a particle size of 0.5-1.5 μm, an average particle size of 0.62 μm, and account for 0.66% of the mass; the second doped particles have a particle size greater than 1.5 μm, an average particle size of 2.64 μm, and account for 99.34% of the mass, with 14.4% of the second doped particles having a particle size greater than 3 μm. The average shape factor of the doped particles is 0.81, and 86.51% of the doped particles have a shape factor not greater than 0.7. Both the fine particles and the doped particles are made of 316 stainless steel, and the mass of the doped particles accounts for 83.85% of the total mass of the fine particles and the doped particles. The crack-resistant particles with a particle size greater than 3 μm are sintered to obtain crack-resistant nodes in the fine layer of the sintered filter medium, while the doped particles with a shape factor not greater than 0.7 are sintered to obtain spheroidal nodes in the fine layer of the sintered filter medium.
[0099] Step A2: After simply mixing the precursor, let it stand for 30 minutes. Then, sonicate the precursor under an ultrasonic power of 100W for 6 minutes. Repeat the standing and sonication process twice to obtain the dispersion precursor. Remove the dispersant clear liquid on top of the dispersion precursor.
[0100] Step A3: Stir and heat the dispersed precursor to constant weight to obtain a dry mixture. The stirring rate is 600 r / min, the vacuum degree is 0.06 MPa, and the temperature is 80℃. Specific raw materials and process parameters are detailed in Tables 1 and 2. Preparation Example 2
[0101] The main difference between Preparation Example 2 and Preparation Example 1 is that, in step A1, the mass of the doped particles is 83.18% of the total mass of the fine particles and the doped particles. Specifically, the first doped particle has a larger average particle size and a higher mass percentage, while the second doped particle has a smaller average particle size and a lower mass percentage. The total average particle size of the doped particles is 1.46 μm. The average shape factor of the doped particles is 0.64, and the proportion of doped particles with a shape factor not greater than 0.7 is 95.32%. Furthermore, the liquid-to-solid volume ratio in the mixed precursor is 5:1.
[0102] Since the mass content of the doped particles is not significantly different, but the average particle size is smaller, in step A2, the number of standing and ultrasonic operations can be appropriately increased to 3 times, and the ultrasonic power can be increased to 200W accordingly, with an ultrasonic time of 3 minutes; in step A3, the stirring rate is increased to 450 r / min, the stirring vacuum degree is 0.04 MPa, and the heating temperature is 70℃. Specific raw materials and process parameters are detailed in Tables 1 and 2. Preparation Example 3
[0103] The main difference between Preparation Example 3 and Preparation Example 1 is that in step A1, the total amount of doped particles added is less. Specifically, the mass of the doped particles is 50.63% of the total mass of the fine particles and the doped particles. The first doped particle has a higher mass percentage, while the second doped particle has a smaller average particle size and a lower mass percentage. The total average particle size of the doped particles is 0.77 μm. The average shape factor of the doped particles is 1.12, and the proportion of doped particles with a shape factor not greater than 0.7 is 75.78%. Furthermore, the liquid-to-solid volume ratio in the mixed precursor is 8:1.
[0104] Because the doped particles have a lower mass content and a smaller average particle size than the total average particle size of the doped particles in Preparation Example 1, in step A2, the number of standing and ultrasonic operations can be appropriately increased to 4 times, the standing time extended to 60 min, and the ultrasonic power correspondingly increased to 300 W, with an ultrasonic time of 12 min. In step A3, the stirring rate is reduced to 300 r / min, the stirring vacuum degree is 0.02 MPa, and the heating temperature is 60 °C. Specific raw materials and process parameters are detailed in Tables 1 and 2. Preparation Example 4
[0105] The main difference between Preparation Example 4 and Preparation Example 3 is that in step A1, the total amount of doped particles added is less. Specifically, the mass of the doped particles is 32.08% of the total mass of the fine particles and the doped particles. The first doped particles account for 100% of the mass, meaning no second doped particles with larger particle sizes are added, and the total average particle size of the doped particles is 0.53 μm. The average shape factor of the doped particles is 1.04, and the proportion of doped particles with a shape factor not greater than 0.7 is 76.37%.
[0106] Because the doped particles have a lower mass content and a smaller average particle size, the settling time in step A2 can be appropriately extended to 90 minutes, and the ultrasonic time can be correspondingly extended to 15 minutes. Specific raw materials and process parameters are detailed in Tables 1 and 2. Preparation Example 5
[0107] The main difference between Preparation Example 5 and Preparation Example 1 is that in step A1, the total amount of doped particles added is slightly higher. Specifically, the mass of the doped particles is 84.92% of the total mass of the fine particles and the doped particles, and the mass percentage of the second doped particles is 100%, meaning that no smaller first doped particles were added. The average particle size of the doped particles is 2.58 μm. The average shape factor of the doped particles is 0.78, and the proportion of doped particles with a shape factor not greater than 0.7 is 89.59%. Specific raw materials and process parameters are detailed in Tables 1 and 2. Preparation Example 6
[0108] The main difference between Preparation Example 6 and Preparation Example 1 is that in step A1, the total amount of doped particles added is slightly higher. Specifically, the mass of the doped particles is 85.05% of the total mass of the fine particles and the doped particles. The first doped particle has a lower mass percentage, while the second doped particle has a higher mass percentage. The total average particle size of the doped particles is 2.21 μm. The average shape factor of the doped particles is 0.61, and the proportion of doped particles with a shape factor not greater than 0.7 is 96.72%.
[0109] Since the amount of doped particles added is not much different from that in Preparation Example 1, but the average particle size is larger, the ultrasonic time in step A2 can be shortened to 4 minutes. Specific raw materials and process parameters are detailed in Tables 1 and 2. Preparation Example 7
[0110] The main difference between Preparation Example 7 and Preparation Example 2 is that in step A1, the fine particles have a particle size of 150-300 nm and an average particle size of 250 nm. The total amount of doped particles added is also less. Specifically, the mass of the doped particles is 72.41% of the total mass of the fine particles and the doped particles. The first doped particle is added in greater quantity, while the second doped particle is added in less quantity. The total average particle size of the doped particles is 1.14 μm. The average shape factor of the doped particles is 0.67, and the proportion of doped particles with a shape factor not greater than 0.7 is 94.85%.
[0111] Since the amount of doped particles added is less and the average particle size is smaller than that in Preparation Example 2, in step A2, the number of standing and ultrasonic operations can be appropriately increased to 4 times, the standing time can be extended to 60 min, and the ultrasonic power can be increased accordingly to 300 W; in step A3, the stirring rate can be reduced to 300 r / min. For specific raw materials and process parameters, please refer to Tables 1 and 2. Preparation Example 8
[0112] The main difference between Preparation Example 8 and Preparation Example 3 is that in step A1, the average shape factor of the doped particles is 1.20, and the proportion of doped particles with a shape factor not greater than 0.7 is 62.17%.
[0113] Because the doped particles have a relatively lower sphericity, in step A2, the settling time is extended to 90 min and the ultrasonic time is extended to 15 min. Specific raw material and process parameters are detailed in Tables 1 and 2. Preparation Example 9
[0114] The main difference between Preparation Example 9 and Preparation Example 2 is that in step A1, the average shape factor of the doped particles is 1.26, and the proportion of doped particles with a shape factor of not more than 0.7 is 54.21%.
[0115] Because the doped particles have a relatively lower sphericity, in step A2, the number of standing and ultrasonic operations can be appropriately increased to 4 times, the standing time extended to 60 minutes, and the ultrasonic power increased to 300W. Specific raw material and process parameters are detailed in Tables 1 and 2. Preparation Example 10
[0116] The main difference between Preparation Example 10 and Preparation Example 2 is that in step A1, the fine particles have a particle size of 150-300 nm and an average particle size of 250 nm, the average shape factor of the doped particles is 0.58, and the proportion of doped particles with a shape factor of no more than 0.7 is 98.34%.
[0117] Since the doped particles have a relatively higher sphericity, the number of settling and ultrasonic operations in step A2 can be appropriately reduced to 2. Specific raw material and process parameters are detailed in Tables 1 and 2. Preparation Example 11
[0118] The main difference between Preparation Example 11 and Preparation Example 4 is that in step A1, the particle size of the doped particles is 0.40-0.55 μm, the average particle size is 0.45 μm, and the mass of the doped particles is 1.8% of the total mass of the fine particles and the doped particles. Specific raw materials and process parameters are detailed in Tables 1 and 2. Preparation Example 12
[0119] The main difference between Preparation Example 12 and Preparation Example 5 is that, in step A1, the particle size of the doped particles is 2-4.5 μm, the average particle size is 3.05 μm, and the mass of the doped particles is 95.03% of the total mass of the fine particles and the doped particles. In step A2, the ultrasonic time is 3 min. Specific raw materials and process parameters are detailed in Tables 1 and 2.
[0120] The particle size distribution, shape parameters, and mass percentage of the doped particles in Examples 1-12 are shown in Table 1 below; the process parameters for Examples 1-12 are shown in Table 2 below.
[0121] Table 1. Raw material parameters for preparation examples 1-12
[0122] Table 2. Process parameters for preparation examples 1-12
[0123] Examples and comparative examples of sintered metal filter media Example 1
[0124] Step S1: Provide coarse particles and a mixture (obtained from Preparation Example 1) and a compression mold. The compression mold includes a compression mandrel, an annular sleeve on its outer periphery, and two plugs at both axial ends of the mandrel and the mixture. An annular cavity is formed between the compression mandrel, the annular sleeve, and the two plugs. The coarse particles and the mixture are filled in the annular cavity. The coarse particles are filled around the outer periphery of the compression mandrel, and the mixture is filled radially outside the coarse particles. The filling thickness of the coarse particles is 499.6 μm, and the filling thickness of the mixture is 423.6 μm. The coarse particles and the mixture are compressed by isostatic pressing to obtain a hollow tubular green embryo. The compression pressure P1 is 120 MPa, the compression time T1 is 100 s, and the coarse particles are carbonyl nickel powder with a particle size of 1-3 μm and an average particle size of 2.3 μm.
[0125] Step S2: Sinter the green blank obtained in step S1 in a vacuum furnace. During sintering, the absolute pressure P2 in the vacuum furnace is 0.008 Pa. The temperature in the vacuum furnace is first uniformly increased from room temperature to a holding temperature of 820°C at a heating rate of 2°C / min. Then, it is held at 820°C for 20 min and cooled to room temperature to obtain the sintered metal filter media pre-finished product.
[0126] Step S3: Cut off both ends of the sintered metal filter media pre-product obtained in step S2 above to obtain the sintered metal filter media. For specific raw material selection and process parameters, please refer to Tables 3 and 4. Example 2
[0127] The main difference between Example 2 and Example 1 is that in step S1, the filling thickness of the coarse particles is 559.4 μm, and the filling thickness of the mixture (obtained from Preparation Example 2) is 421.7 μm; the compression pressure P1 is 90 MPa, the compression time T1 is 90 s, and the coarse particles are carbonyl nickel powder with a particle size of 3-6 μm and an average particle size of 4.6 μm; in step S2, the absolute pressure P2 in the vacuum furnace is 0.004 Pa, the temperature in the vacuum furnace is increased from room temperature to the holding temperature at a heating rate of 5 °C / min, the holding temperature is 800 °C, and the holding time is 30 min. Specific raw material selection and process parameters are detailed in Tables 3 and 4. Example 3
[0128] The main difference between Example 3 and Example 1 is that in step S1, the filling thickness of the coarse particles is 536.1 μm, and the filling thickness of the mixture (obtained from Preparation Example 3) is 505.0 μm; the compression pressure P1 is 70 MPa, the compression time T1 is 60 s, and the coarse particles are carbonyl nickel powder with a particle size of 6-10 μm and an average particle size of 8.2 μm; in step S2, the absolute pressure P2 in the vacuum furnace is 0.002 Pa, the temperature in the vacuum furnace is increased from room temperature to the holding temperature at a heating rate of 8 °C / min, the holding temperature is 780 °C, and the holding time is 40 min. Specific raw material selection and process parameters are detailed in Tables 3 and 4. Example 4
[0129] The main difference between Example 4 and Example 3 is that in step S1, the filling thickness of the coarse particles is 539.1 μm, and the filling thickness of the mixture (obtained from Preparation Example 4) is 501.7 μm; in step S2, the holding time is shortened to 30 min. For specific raw material selection and process parameters, please refer to Tables 3 and 4. Example 5
[0130] The main difference between Example 5 and Example 1 is that in step S1, the filling thickness of the coarse particles is 515.7 μm, the filling thickness of the mixture (obtained from Preparation Example 5) is 439.9 μm, and the compression time T1 is 120 s; in step S2, the holding time is 40 min. For specific raw material selection and process parameters, please refer to Tables 3 and 4. Example 6
[0131] The main difference between Example 6 and Example 1 is that in step S1, the filling thickness of the coarse particles is 506.0 μm, the filling thickness of the mixture (obtained from Preparation Example 6) is 437.1 μm, and the compression time T1 is 120 s; in step S2, the holding time is 30 min. For specific raw material selection and process parameters, please refer to Tables 3 and 4. Example 7
[0132] The main difference between Example 7 and Example 2 is that in step S1, the filling thickness of the coarse particles is 139.0 μm, the filling thickness of the mixture (obtained from Preparation Example 7) is 27.2 μm, and the compression pressure P1 is 80 MPa. Specific raw material selection and process parameters are detailed in Tables 3 and 4. Example 8
[0133] The main difference between Example 8 and Example 3 is that, in step S1, the filling thickness of the coarse particles is 1311.9 μm, and the filling thickness of the mixture (obtained from Preparation Example 8) is 2463.5 μm; in step S2, the holding time is shortened to 30 min. For specific raw material selection and process parameters, please refer to Tables 3 and 4. Example 9
[0134] The main difference between Example 9 and Example 2 is that in step S1, the filling thickness of the coarse particles is 521.4 μm, the filling thickness of the mixture (obtained from Preparation Example 9) is 430.2 μm, and the compression pressure P1 is 80 MPa; in step S2, the holding time is 20 min. For specific raw material selection and process parameters, please refer to Tables 3 and 4. Example 10
[0135] The main difference between Example 10 and Example 2 is that in step S1, the filling thickness of the coarse particles is 1140.9 μm, the filling thickness of the mixture (obtained from Preparation Example 10) is 912.3 μm, and the compression time is extended to 100 s; in step S2, the holding time is extended to 40 min. For specific raw material selection and process parameters, please refer to Tables 3 and 4. Example 11
[0136] The main difference between Example 11 and Example 4 is that there are no coarse particles. In step S1, the mixture obtained in Example 4 is directly compressed at 8 MPa for 50 seconds to obtain a hollow tubular green embryo. In step S2, the holding time is shortened to 25 minutes. For specific raw material selection and process parameters, please refer to Tables 3 and 4. Example 12
[0137] The main difference between Example 12 and Example 5 is that there are no coarse particles. In step S1, the mixture obtained in Example 5 is directly compressed at 30 MPa for 80 seconds to obtain a hollow tubular green embryo. In step S2, the holding time is shortened to 30 minutes. For specific raw material selection and process parameters, please refer to Tables 3 and 4. Comparative Example 1
[0138] The main difference between Comparative Example 1 and Example 11 is that in step S1, only fine particles with a particle size of 50-150 nm and an average particle size of 100 nm are compressed at a compression pressure of 8 MPa for 50 s to obtain a hollow tubular green embryo. In this case, no doped particles are dispersed in the fine particles, and no mixture is formed. In step S2, the holding time is shortened to 20 min. For specific raw material selection and process parameters, please refer to Tables 3 and 4. Comparative Example 2
[0139] The main difference between Comparative Example 2 and Example 11 is that in step S1, the mixture obtained in Example 11 is compressed at a compression pressure of 10 MPa for 50 s to obtain a hollow tubular green embryo, wherein the average particle size of the doped particles in the mixture is 0.45 μm and the mass percentage is only 1.8%; in step S2, the holding time is shortened to 22 min. For specific raw material selection and process parameters, please refer to Tables 3 and 4. Comparative Example 3
[0140] The main difference between Comparative Example 3 and Example 12 is that in step S1, the fine particles obtained in Example 12 are compressed at a pressure of 30 MPa for 100 s to obtain a hollow tubular green embryo, wherein the average particle size of the doped particles in the mixture is 3.05 μm and the mass percentage is 95.03%; in step S2, the holding time is 40 min. For specific raw material selection and process parameters, please refer to Tables 3 and 4.
[0141] Table 3 Summary of relevant parameters for coarse particles in Examples 1-10
[0142] Table 4 Summary of process parameters for Examples 1-12 and Comparative Examples 1-3
[0143] Performance testing methods and results I. Morphological parameters of sintered metal filter media products The SEM images of the outer and inner surfaces of the sintered metal filter media products prepared in Examples 1-12 and Comparative Examples 1-3, combined with manual measurement or NanoMeasure and ImageJ software, can be used to measure parameters such as the average particle size, surface distribution density, area ratio, and shape factor of the pinned nodes. Specific testing methods are detailed in the invention description section.
[0144] In addition, the total thickness and the thickness of the fine layer of sintered metal filter media products can be directly measured from the cross-sectional SEM image of the product or by using a thickness gauge.
[0145] II. Cutting and Cracking Performance of Sintered Metal Filter Media Products The testing method is as follows: 10 hollow tubular sintered metal filter media products were provided for each of Examples 1-12 and Comparative Examples 1-3. Each sintered metal filter media product was cut 10 times (10 positions along the axis), that is, a total of 100 cuts were made for the products prepared in each example and comparative example (the cuts were made on both the left and right sides, for a total of 200 cuts). The cuts were observed by the naked eye or under a magnification device of about 10-100 times to see if there was obvious cracking. The number of axial cracks that occurred from the cut position was counted, and the corresponding cutting cracking probability could be calculated.
[0146] III. Performance of Sintered Metal Filter Media Products 3.1 Pressure Holding Performance of Sintered Metal Filter Media Products The testing method is as follows: First, filter elements made from sintered metal filter media prepared in Examples 1-12 and Comparative Examples 1-3 are impregnated with molten paraffin and cooled to seal the membrane pores of the filter media. Then, high-pressure water is injected into the hollow interior of the filter element. The pressure of the high-pressure water is gradually increased from 1 MPa, increasing by 1 MPa each time, and each pressure is maintained for 1 hour until the pressure of the high-pressure water suddenly drops (the filter element ruptures), at which point the maximum pressure resistance value of the corresponding filter element is measured. For example, when the pressure of the high-pressure water is 5 MPa, the pressure holding is passed; however, when the pressure of the high-pressure water is increased to 6 MPa, the pressure of the high-pressure water drops suddenly. It can be preliminarily determined that the pressure holding pressure of the filter element is not less than 5 MPa and less than 6 MPa. Further, the pressure of the high-pressure water is increased in increments of 0.1 MPa until the accurate pressure holding pressure is measured. When measuring the pressure holding pressure of the filter element made from the sintered metal filter medium prepared in Comparative Example 3, the filter element was found to be ruptured when the pressure of the high-pressure water was 1 MPa. Therefore, the pressure holding pressure was further reduced by 0.1 MPa until the pressure holding pressure was measured.
[0147] To clarify, during the pressure holding test, the downstream pressure of the filter element is atmospheric pressure, and the upstream pressure is the pressure of high-pressure water. At this time, the pressure difference between the upstream and downstream sides of the filter element is almost equal to the pressure of the high-pressure water. In fact, under the filtration conditions of supercritical carbon dioxide, the pressure difference between the upstream and downstream sides of the filter element generally does not exceed 2 MPa. Therefore, when the pressure holding pressure of the filter element reaches more than 10 MPa, it will almost not be damaged by the pressure during use (even if pressure fluctuations cause a sudden increase in pressure). Therefore, tests for higher pressure holding pressures are no longer conducted.
[0148] 3.2 Vickers hardness of fine layers Test Procedure: The Vickers hardness can be measured using an Innovatest Falcon 507 microhardness tester. The test method involves selecting an appropriate load (0.1 kg in this application) and holding time (generally 10-15 s) based on the characteristics of the material being tested. After the test, the size of the indentation is measured using software, and the Vickers hardness value is displayed. Of course, results obtained from other Vickers hardness testing devices conforming to relevant standards, besides the aforementioned model, are also acceptable. It should be noted that when measuring the Vickers hardness of a fine layer, the indentation should be located on the outer surface of the fine layer.
[0149] 3.3 Initial bubble point of IPA in sintered metal filter media Test procedure: First, completely impregnate the sintered metal filter media with IPA; then, slowly introduce gas (such as nitrogen) and gradually increase the pressure. The pressure at which the first continuous bubble appears at the outlet is the initial bubble point of the IPA. Other operational details can be found in ASTM F316-70 or ISO 2942:2018.
[0150] 3.4 Porosity of sintered metal filter media For detailed testing methods, please refer to the invention description section.
[0151] The test results are recorded in Tables 5 to 7.
[0152] Table 5 Characterization results of fine layers
[0153] Table 6 Characterization results of the coarse layer
[0154] Table 7 Performance test results of sintered metal filter media Total thickness / μm Fine layer thickness / μm Porosity of filter media / % IPA initial bubble point / kPa Probability of cracking during cutting / % Hardness of the fine layer / HV0.1 Holding pressure / MPa Example 1 732.1 346.1 34.6 323.4 2 108.3 >10 Example 2 776.7 344.5 31.9 334.5 2 114.2 >10 Example 3 826.8 412.6 25.2 363.2 3 125.8 >10 Example 4 814.5 401.8 22.1 369.6 8 143.2 >10 Example 5 759.7 361.3 39.8 327.8 3 104.4 8.8 Example 6 751.9 361.0 37.5 330.1 4 106.8 9.1 Example 7 129.6 22.2 27.0 51.8 4 95.1 4.8 Example 8 3026.1 2012.6 24.7 497.5 9 157.3 >10 Example 9 743.7 344.5 32.8 330.1 8 118.9 >10 Example 10 1626.7 745.3 33.5 313.2 3 110.3 9.5 Example 11 411.2 411.2 21.3 332.6 9 141.7 9.2 Example 12 353.7 353.7 38.6 295.0 6 102.1 7.1 Comparative Example 1 348.3 348.3 11.2 354.0 78 217.3 / Comparative Example 2 350.9 350.9 14.5 339.3 62 165.4 / Comparative Example 3 357.6 357.6 60.7 280.3 6 67.3 0.4 Data Analysis and Conclusions Comparing the performance test results of Examples 1-3 and Comparative Example 1, it can be seen that when there are no pinning nodes in the porous structure of the fine layer, the probability of cutting and cracking of the corresponding sintered metal filter media product reaches 78%. Comparing the performance test results of Examples 1-3 and Comparative Example 2, it can be seen that even if the porous structure of the fine layer contains pinning nodes, the particle size is too small and the surface distribution density is too low (i.e., the pinning nodes are both small and few). Although the probability of cutting and cracking of the corresponding sintered metal filter media product is reduced, it is still as high as 62%. In summary, when the sintered metal filter... When a media product lacks pinning nodes, or when it contains pinning nodes but the average particle size of the pinning nodes is less than 0.5 μm and the surface distribution density is less than 1 per 10 square micrometers, correspondingly, no soft areas are formed in the sintered metal filter media product. Alternatively, the soft areas in the sintered metal filter media product are small in volume and few in number. When these soft areas are cut, microcracks are easily formed. Furthermore, once formed, the microcracks are not blocked in a timely and effective manner, but instead spread or extend rapidly axially. The final result is that the probability of the filter media product cracking upon cutting is very high.
[0155] Comparing the performance test results of Examples 1-3 and Comparative Example 3, it can be seen that even if the porous structure of the fine layer contains pinned nodes, if the particle size is too large and the surface distribution density is too high (i.e., the pinned nodes are both large and numerous), although the probability of cutting and cracking of the corresponding sintered metal filter media product is less than 10%, its mechanical properties drop sharply. The pressure holding pressure of the filter element made from it is only 0.4 MPa, which is less than the pressure difference under supercritical filtration conditions and cannot meet the pressure resistance requirements under supercritical filtration conditions. When the average particle size of the pinned nodes in the sintered metal filter media product is greater than 2.6 μm and the surface distribution density is more than 10 per 10 square micrometers, the soft area in the sintered metal filter media product is large in volume and numerous, resulting in very low overall hardness and poor pressure resistance of the filter media, which cannot meet the pressure difference requirements of supercritical fluid filtration conditions.
[0156] Comparing the performance test results of Examples 1-3 and Example 4, it can be seen that when the average particle size of the pinned nodes in the porous structure of the fine layer is less than 0.6 μm, the volume of the soft region in the porous structure of the fine layer is relatively small, and the blocking effect on the propagation of microcracks is relatively weaker, and the probability of cutting cracking increases to nearly 10%. Comparing the performance test results of Examples 1-3 and Example 5, it can be seen that when the average particle size of the pinned nodes in the porous structure of the fine layer is greater than 2.0 μm, the probability of cutting cracking does not change much, but due to the relatively large volume of the soft region, the pressure resistance of the product deteriorates significantly, and its holding pressure drops from over 10 MPa to 8.8 MPa. The probability of cutting cracking of the sintered metal filter media products prepared in Examples 1-3 is all below 3%, and the holding pressure is all above 10 MPa.
[0157] Comparing the performance test results of Examples 4 and 11, and comparing the performance test results of Examples 5 and 12, it can be seen that when the sintered metal filter media products have no coarse layer and the porous structure of the fine layer is basically the same (mainly referring to the particle size distribution and surface distribution density of the pinned nodes being basically the same or similar), the cutting crack probability of the sintered metal filter media products is not much different, but the pressure resistance of the sintered metal filter media products without coarse layers is worse, which is manifested in a lower holding pressure value.
[0158] The above performance test results show that when the porous structure of the fine layer of the sintered metal filter medium has pinned nodes, and the particle size of the pinned nodes is not less than 0.4 μm, the average particle size is 0.5-2.6 μm, the surface distribution density is 1-10 nodes per 10 square micrometers, and the area ratio is not more than 85%, the probability of cutting and cracking of the sintered metal filter medium product can be stably controlled below 10%. Furthermore, the filter element made from the sintered metal filter medium product also exhibits sufficiently high mechanical stability under high-pressure filtration conditions, with holding pressures all above 4.8 MPa. Moreover, the sintered metal filter medium product prepared in Example 8 has a very low flux, a very high bubble point (close to 500 kPa), and a very small pore size, making it suitable for trapping small-sized (e.g., 10 nm) particulate contaminants. The sintered metal filter medium product prepared in Example 7 has a very low bubble point (approximately 50 kPa) and a relatively large pore size, making it suitable for treating fluids containing larger (e.g., 100 nm) particulate contaminants and providing a higher flux.
[0159] The general steps for fabricating filter element 100 from the sintered metal filter media obtained in Examples 1-12 are as follows: The closed end plate 20 and the connector component 30 with a hollow channel 31 are welded to both ends of the hollow tubular sintered metal filter media 10, respectively. The hollow channel 31 of the connector component 30 communicates with the surface of the coarse layer of the sintered metal filter media 10 away from the fine layer. A schematic diagram of the filter element 100 is shown below. Figure 3 The filter element 100 and the housing 200 are assembled together to form a filter, wherein the housing 200 has a connector 210, such as... Figure 4 As shown. During filtration, the supercritical carbon dioxide to be filtered is introduced into the hollow interior of the filter element 100 through the hollow channel 31 of the connector component 30, and passes through the coarse layer and the fine layer in sequence. Large particulate pollutants and small particulate pollutants are intercepted in sequence, and the clean supercritical carbon dioxide flows out from the surface of the fine layer away from the coarse layer (the arrow indicates the direction of fluid flow), and finally is discharged from the connector 210 of the outer shell 200.
[0160] The technical features of the above embodiments can be combined in any way. For the sake of brevity, not all possible combinations of the technical features in the above embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0161] The embodiments described above are merely illustrative of several implementations of the present invention and should not be construed as limiting the scope of the invention. It should be noted that various modifications and improvements can be made without departing from the concept of the present invention, and these all fall within the protection scope of the present invention.
Claims
1. A sintered metal filter medium comprising at least a fine layer, the sintered metal filter medium being in a hollow tubular structure; characterized in that, the fine layer is a porous structure, the porous structure of the fine layer having pinning nodes; the pinning nodes have a particle size of no less than 0.4 μm, an average particle size of 0.5-2.6 μm, a surface distribution density of 1-10 per 10 square microns, and an area ratio of no more than 85%; the sintered metal filter medium has an IPA initial foaming point of 50-500 kPa.
2. The sintered metal filter medium of claim 1, wherein, the pinning nodes have an average particle size of 0.6-2 μm, and a surface distribution density of 2-7 per 10 square microns.
3. The sintered metal filter medium of claim 1, wherein, the pinning nodes comprise at least first pinning nodes having a particle size of 0.5-1.5 μm and second pinning nodes having a particle size greater than 1.5 μm, and the first pinning nodes have a quantity ratio of 30-90%.
4. The sintered metal filter medium of claim 3, wherein, the second pinning nodes comprise blocking nodes having a particle size of no less than 3 μm, and the number of the blocking nodes is no more than 10% of the number of all pinning nodes and no less than 3% of the number of all pinning nodes.
5. The sintered metal filter medium of claim 1, wherein, the pinning nodes have an average shape factor of no more than 1.
15.
6. The sintered metal filter medium of claim 5, wherein, the pinning nodes comprise spherical-like nodes having a shape factor of no more than 0.7, and the spherical-like nodes have a quantity ratio of no less than 60%.
7. The sintered metal filter medium of claim 1, wherein, the average distance between adjacent two pinning nodes is 0.2-2 μm.
8. The sintered metal filter medium of claim 1, wherein, the sintered metal filter medium further comprises a coarse layer located radially inside the fine layer, the coarse layer being a porous structure, and the coarse layer and the fine layer are sintered into one body; or, the sintered metal filter medium further comprises a coarse layer located radially inside the fine layer and at least one functional layer located radially inside the coarse layer, the coarse layer and the functional layer are both porous structures, the functional layer, the coarse layer and the fine layer are sintered into one body, and the functional layer is at least one of a pre-filtering layer, a reinforcing layer and a separation layer.
9. The sintered metal filter medium of claim 8, wherein, a surface of the coarse layer away from the fine layer is an inner surface of the sintered metal filter medium, and the coarse layer has a pore area ratio of 10-40% on the surface away from the fine layer.
10. The sintered metal filter medium of claim 9, wherein, the average width of a sintering neck on the surface of the coarse layer away from the fine layer is 0.2-6 μm, the average maximum Fretter diameter of a pore is 0.5-7 μm, and the ratio of the maximum Fretter diameter to the minimum Fretter diameter of the pore is 1.2-5.
11. The sintered metal filter medium of claim 9, wherein, the sintered metal filter medium has a thickness of 120-3000 μm, and the thickness of the fine layer is 1 / 6-2 / 3 of the thickness of the sintered metal filter medium.
12. The sintered metal filter medium of claim 8, wherein, the sintered metal filter medium has a porosity of 20-40%.
13. The sintered metal filter medium of claim 1, wherein, the fine layer is formed by sintering a mixture, the mixture comprising at least fine particles and doping particles, the doping particles forming the pinning nodes of the porous structure of the fine layer, and the doping particles have a particle size greater than that of the fine particles.
14. A method of producing a sintered metal filter medium as claimed in any one of claims 1-13, characterized in that, comprising the following steps: S1: providing a mixture composed of fine particles and doping particles uniformly dispersed therein, compressing the mixture to obtain a hollow tubular green body, and preparing the mixture by the following steps: A1-mixing a dispersant with surface tension not more than 30 mN / m with fine particles and doping particles to obtain a mixed precursor, A2-resting the mixed precursor, and then performing ultrasonic operation on the mixed precursor to obtain a dispersed precursor, A3-stirring and heating the dispersed precursor to dry to obtain a mixture; wherein the fine particles have a particle size of 50-300 nm, the doping particles have a particle size not less than 0.4 μm and an average particle size of 0.5-2.6 μm, and the mass of the doping particles is 15-85% of the total mass of the fine particles and the doping particles; S2-sintering the green compact obtained in S1 to obtain a sintered metal filter medium pre-product; S3-cutting at least one end of the sintered metal filter medium pre-product obtained in S2 to obtain a sintered metal filter medium.
15. The method of making a sintered metal filter medium according to claim 14, wherein, Step A2 is repeated 2-4 times; and / or, in step A2, the resting time is 30-90 min, and the ultrasonic power is 100-300 W and the ultrasonic time is 3-15 min.
16. The method of making a sintered metal filter medium according to claim 14, wherein, In step S1, coarse particles with a particle size of 1-10 μm are further provided, wherein the mixture is located radially outside the coarse particles, and the coarse particles and the mixture are compressed to obtain a hollow tubular green compact, the fine particles and the doping particles are made of stainless steel, and the coarse particles are made of nickel or carbonyl nickel; in step S2, the sintering process comprises a heating stage and a subsequent holding stage, the heating stage is uniformly raised from the ambient temperature to 780-820 ℃ at a rate of 2-8 ℃ / min, and the holding stage is held at 780-820 ℃ for 20-40 min.
17. The method of making a sintered metal filter medium according to claim 14, wherein, The dispersant is selected from one or more of methanol, ethanol, n-propanol, isopropanol or n-butanol, in step A1, the liquid to solid volume ratio is 2:1-8:1; in step A3, before heating and stirring, the dispersant supernatant above the dispersed precursor is removed first, the stirring rate is 300-600 r / min, the vacuum degree during stirring is 0.02-0.06 MPa, and the temperature is 60-80 ℃.
18. A filter cartridge, characterized by The filter element comprises the sintered metal filter medium according to any one of claims 1-13.
19. A method of filtering supercritical carbon dioxide, characterized by, During filtration, supercritical carbon dioxide is passed through the sintered metal filter medium according to claims 1-13.
Citation Information
Patent Citations
Method for preparing aluminum oxide-based ceramic hollow fibrous membrane
CN101905121A
Sintered porous material having nodes and fibers of different materials, with different sintering points, and related methods of preparation and use
CN111542407A
Polytetrafluoroethylene degerming film as well as preparation method and application thereof
CN116585906A
Silicon carbide nanowire nanofiltration membrane as well as preparation method and application thereof
CN118267861A
Porous sintered body
JP2019196291A